MODEL PENGEMBANGAN PARIWISATA TERPADU PADA ERA PANDEMI MELALUI PERANAN VIRTUAL REALITY EXPERIENCE DAN CITRA DESTINASI: Kajian Penelitian di Pulau Belitung, Indonesia - Echo Perdana Kusumah, - (2022)
The tourism sector is one of Indonesia's most important economic activities, as indicated by the establishment of a Special Economic Zone for Tourism. The COVID-19 disease outbreak, on the other hand, has become one of the impediments to these tourism activities, giving rise to alternative tourism via virtual reality technologies. This study's objective was to investigate the role of Virtual Reality Experience (VRE), travel motivation, travel constraints, risk perception, and destination image on revisit intentions during the COVID-19 period. This research method is quantitative, and the respondents are Indonesian visitors who have visited the tourism destinations on Belitung Island. Using convenience sampling, a total of 525 samples were collected and analyzed using a structural equation model (SEM). According to the findings, the benefits and convenience of VRE positively affect the image of the destination and the intention to return, implying that using a tool in the form of a VR box, computer, or smartphone through videos uploaded via YouTube media can improve the image of the destination and tourists' desire to revisit tourist destinations on Belitung Island. During the COVID-19 pandemic, the operation of VR technology must be enhanced because it is still a new technology that must be adjusted initially. This study indicated that tourist motivations, such as the desire for relaxation, excitement, adventure, and entertainment, had a beneficial effect on the image of the destination. It is vital to provide tourism activities and infrastructure that support entertainment indicators since the entertainment component is the most influential motivator. In addition, tourists might negotiate travel restrictions to boost their intention to return. The perception of risk can moderate travel motivation and the destination's image in relation to the likelihood of a return visit. This study also discovered that destination image can mediate the effects of VRE and travel motivation on the intention to return. This study reveals how virtual reality can help improve the image of a tourist destination in instances like the COVID-19 pandemic or other comparable pandemics.